All that jazz - Gara L. Lampley (Akademisk Kvarter, 2015)
When Baker was offered an opportunity to move to, Paris, for her dance talents, she did not hesitate to take the chance. Baker arrived in Paris the summer of 1925, during the height of France’s obsession with American jazz music and all things exotic. Immediately after her famous performance on October 2, 1925, Baker appeared in a jazz club wearing an ice-blue dress, cut on the bias. It had been selected for her from a Paris design house. This glamorous side of Baker quickly dispelled the notion of her as primitive. Her body type and cinnamon skin proved to be the perfect model for the masters of fashion. Baker quickly became a woman who others wanted to copy.